1994
DOI: 10.3109/07357909409023025
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility Study of Extended Chemotherapy for Locally Advanced Non-Small Cell Lung Cancer: A Phase II Trial of Cancer and Leukemia Group B

Abstract: The purpose of this study was to determine the feasibility of additional chemotherapy beyond 5 weeks of vinblastine-cisplatin followed by radiation therapy for patients with stage III non-small cell lung cancer. In this randomized phase II trial, the goal was to determine, in a similar population of patients, the toxicity of either of two additional chemotherapy programs. Ninety-one patients with stage III non-small cell lung cancer received the same induction regime of vinblastine/cisplatin/radiotherapy. In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…In several trials, improved 1-and 2-year overall survival rates in favor of the concurrent arm were reported [18][19][20][21][22][23].…”
Section: Radiochemotherapy In Locally Advanced Nsclcmentioning
confidence: 99%
“…In several trials, improved 1-and 2-year overall survival rates in favor of the concurrent arm were reported [18][19][20][21][22][23].…”
Section: Radiochemotherapy In Locally Advanced Nsclcmentioning
confidence: 99%
“…In several trials improved 1- and 2-year overall survival rates in favour of the concurrent arm were reported [1723]. …”
Section: Sequential Versus Concurrent Radiochemotherapymentioning
confidence: 99%
“…Randomised clinical trials and metaanalyses have generally shown trends in favour of combination chemoradiotherapy compared with radiotherapy alone [14][15][16][17][18][19][20][21][22][23], as well as concomitant compared with sequential chemoradiotherapy [24][25][26][27][28][29][30]. However, many patients are considered unsuitable for chemoradiotherapy, particularly with concurrent administration, due to poor performance status or the presence of serious comorbidities.…”
Section: Introductionmentioning
confidence: 99%